Implementation of the Module Development Program for the Increase of Tourism Awareness for Souvenir Merchants in Bukittinggi City - Aini, Wirdatul; Hayatunnufus, Hayatunnufus (Universitas Negeri Semarang, 2019)
This research is motivated by the low awareness of souvenir merchant tourism. This study aims to produce the implementation of module conscious tourism development for souvenir merchants include: (1) test validity, practicality, and effectiveness test of tourism-awareness modules for souvenirs traders, (2) process of module conscious tourist development and (3) produce guide the implementation of module conscious development of tourist souvenir merchants. The research approach is used quantitatively. Research subjects are education experts, city market office Bukittinggi, and merchants’ souvenirs. The collection of validity test data, the practicability of the tourism conscious module is obtained from educational experts, city market service and to test the effectiveness of modules obtained from souvenir merchants. Research findings can be put forward as follows: (1) the content validity test data, and module practicality module is very good, and the development of the tourism conscious module for the souvenir merchants proved perfective to increase the conscious tourist souvenir merchants, (2) the process of developing a module for increasing tourism awareness for souvenir merchants is designed based on the needs of souvenir merchants on the behavior that must be owned by souvenir merchants to participate, actively participate in developing the city of Bukittinggi as a tourist area, and (3) generated guidance implementation of the development of module conscious tourist souvenir merchants. This research is useful to foster souvenir merchant participation in the tourism industry and promote souvenir products.